Endoscopic spine surgery - Kim, Daniel H.; Choi, Gun; Lee, Sang-Ho; Fessler, Richard G. (Thieme, 2018)
Endoscopic technology has advanced to the point where practitioners can now access, visualize, and treat spine pathologies previously only accessible through open surgical approaches. Endoscopic Spine Surgery 2nd Edition provides a comprehensive background on endoscopic spine surgery and covers an unparalleled number of minimally invasive spine procedures that have revolutionized the spine treatment paradigm. Readers will greatly benefit from many years of expertise and wisdom shared by master spine surgeons Daniel Kim, Gun Choi, Sang-Ho Lee, and Richard Fessler, and their expert contributors